Personality Traits, Emotional Intelligence, Love Of Money, Financial Self-Efficacy, And Lifestyle On Financial Behavior - Lestari, Winda Rika; Triandini, Khofifah; Saputra, Richard; Putri, Reisa Dyasvaro Zulanda (Universitas Dharma Wacana, 2023)
This research aims to determine the influence of personality traits, emotional intelligence, love of money, financial self-efficacy, and lifestyle on financial behavior. The type of research used is associative with a quantitative approach. The population in this study were students. The type of sampling used in this research is a nonprobability sampling method using snowball sampling and purposive sampling techniques. The data analysis method used is multiple linear regression analysis. The research results show that personality traits, emotional intelligence, love of money, financial self-efficacy and lifestyle have a significant positive effect on financial behavior. These results indicate that students who have good personality traits, good emotional intelligence, a high level of love of money, a good life style will have good financial behavior too. Furthermore, the higher a person's self-efficacy, the more responsible that person will be for their financial behavior.